PELAKSANAAN HIBAH DAN WASIAT DIKALANGAN MASYARAKAT KABUPATEN BONE - Ahmad Supandi Patampari (Al-Risalah: Jurnal Hukum Keluarga Islam (Ahwal Al-Syakhsiyah), 2021)
Abstract This study aims to determine the construction of the implementation of the grant and will among people in Bone regency, to know how the form of grants and wills, strategies communities in the implementation of the grant and the will and the reason people districts Bone is using grants and wills in the division of inheritance compared with the Islamic inheritance system in Bone regency. The results showed that Form grants and testament in the District public Bone is rather the form of grants that are written but there is also using oral, that will, bone people tend to use the oral form of the posts. Community strategies at the time of grant and will bring the grantee or recipient of his testament and presented witnesses who truly believed at the time when the Islamic marriage contract and grant deed or a will. The grant can be directly given by penghibah and will also be directly awarded regardless wait until pewasiat died.